Presentation and Outcome of Surgical Treatment of Malrotation in Children (Journal of Chittagong Medical College Teachers' Association, 2012)
Introduction  : Malrotation is a common anomaly in the pediatric age group which includes a wide spectrum of anomalies of Rotation. Both acute and chronic presentations are common. Atypical malrotation not having all the features of classic mal Rotation is frequently found which a diagnostic dilemma and the management varies from centre to centre.Materials and Methods : The medical records of all patients with symptomatic malrotation, who underwent surgery between July 2001 to June 2011, were retrospectively reviewed. Patients’ presentation, management, operative findings and complications were evaluated.Results : 68 patients underwent surgery for malrotation at a median age of 2 years. Male to female ratio was 2:1. 28(41%) presented with acute symptoms and 40(59%) with chronic symptoms. 54(79%) patients had vomiting, 36 (%3%) presented with abdominal distension, 19(28%) had recurrent abdominal pain. Diagnostic laparoscopy was done in 7(10%) patients. Ladd’s band was found in 16(24%) patients and Volvulus was found at the time of surgery in 5(7%) patients. 5(7%) patients also had associated anomalies. Ladd’s procedure was done in 15(22%) patients and 23(34%) patients needed resection and anastomosis. Median length of hospital stay was 10 days. Postoperative bowel obstruction was seen in 4(6%) patients and 2(3%) patients had post operative intussusceptions. There was 2(3%) death due to septicaemia with volvulus and gangrenous gut.Conclusion : The clinical presentation and anatomy of malrotation occurs along a wide clinical and anatomic variations and a high index of suspicion is required to prevent a delay in diagnosis.JCMCTA 2011; 22(2): 17-21